Chronic low back pain: a representation of liminality in illness identity and professional identity - Ampiah, Josephine Ahenkorah (2022)
Background: Chronic low back pain (CLBP) accounts for most of the negative consequences associated with low back pain (disability, costs, productivity). Certain risk factors, particularly pain beliefs, facilitate the occurrence and progression of CLBP. Patients’ beliefs may be influenced by healthcare professionals’ (HCPs’) beliefs and the sociocultural context. HCPs’ beliefs are critical to the uptake of recommended biopsychosocial approaches for CLBP. However, the beliefs of Ghanaian patients and HCPs are unknown. Therefore, this research explored patients’ and HCPs’ CLBP beliefs and how these affected CLBP management in Ghana.